2008
DOI: 10.1002/jor.20610
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint biomechanics following arthroscopic partial meniscectomy

Abstract: We investigated spatiotemporal data, joint kinematics, and joint kinetics during gait in a group of subjects who had recently undergone arthroscopic partial meniscectomy and compared the results to those of healthy controls. Gait analysis was performed on 105 pain-free meniscectomy patients and 47 controls, walking at a self-selected speed. The meniscectomy population was comparable to controls in spatiotemporal parameters and knee kinematics. However, they had reduced range of motion (ROM) and lower peak mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 33 publications
(51 reference statements)
6
72
1
3
Order By: Relevance
“…For example, persons post-meniscectomy are at increased risk of developing knee OA [13]. A large cross-sectional study of individuals post-APM found an 11% increase in peak KAM during walking when compared with healthy matched controls [14]. It is widely believed this elevated peak KAM contributes to the onset of knee OA in this population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, persons post-meniscectomy are at increased risk of developing knee OA [13]. A large cross-sectional study of individuals post-APM found an 11% increase in peak KAM during walking when compared with healthy matched controls [14]. It is widely believed this elevated peak KAM contributes to the onset of knee OA in this population.…”
Section: Discussionmentioning
confidence: 99%
“…25 The results from this study suggest that interventions targeting gait biomechanics 1 following APMM may result in improved patient outcomes. Interventions such 2 as gait retraining [18,31], valgus thrust braces [19,29], modified footwear [14] 3 and lateral wedge insoles [15,16] have been shown to reduce knee adduction 4 moments. These may reduce the risk of the APMM patients developing medial 5 tibiofemoral osteoarthritis osteoarthritis, which should be the focus of future 6 studies.…”
mentioning
confidence: 99%
“…Our findings have shown that these regions were not only susceptible to impact-induced damage, they were also more inclined towards post-traumatic degeneration. Apart from the altered knee joint biomechanics arising from meniscectomy, 37 the inferior resistance of menisci-covered regions, against impact-induced damage and degeneration, is a potential factor that may contribute in part to the meniscectomy model of OA.…”
Section: Discussionmentioning
confidence: 99%